Approaching a Successful Interior Design Atmosphere for Retail Clothing Stores Case of Dereboyu Street, Lefkoşa - Rezanejad, Nazanin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Shopping is one of the attractive activities in people’s every day’s life. Because of the importance of this activity, the stores can play a significant role for shoppers. Coordinately, a successful atmosphere of the stores can affect the shoppers and attract them. Atmosphere is a language of interior space. It is the value, which belongs directly to human’s emotion without any boundary. Human think, feel, imagine, dream and this routine processes are significant to clarify characteristics of human being. As a matter of fact, one of the aims of interior design is to increase the quality of the spaces. Several elements are the reason of creation of atmosphere. In between these elements interior design and ambient factors playing important roles which are related directly with the human being emotions. These elements can give meaning to any space and affect the human being psychology, feeling and senses. Successful atmosphere can create a sense of confidence for the users. Design and ambient factors are one of the elements which can control the atmosphere of the space. According to these importance’s, this study explores the effect of interior design elements due to creating appropriate atmosphere of the interior spaces of retail stores. The general problem statement deals with the lack of the knowledge of store’s owners about the creating of the useful interior design and successful atmosphere of the retail clothing stores. The aim of this study is to find a design guideline for retail clothing store through the main shopping streets of cities. Quantitative method which is based on the observation of outer and qualitative method which deals with the literature survey of the study can lead the research to achieve the results to have the design guideline for retail clothing stores. Literature survey mainly based on three main parts. In the first part, general information of stores, history and development of retailing were considered. Different functions which can be exist in retail stores were explained and atmosphere of the stores were mentioned which could contain external and internal factors. Second part deals with general information about retail clothing stores, interior design, effect of gender, perception and space organizations on the retail clothing stores. The investigation of interior design of clothing retail stores along the main shopping street of Lefkoşa were explored. Retailing stores were selected for the study, analyzed and observed to achieve the founding of the study. Men, women and unisex clothing stores along the Dereboyu Street in Lefkoşa were selected the analysis. The average of the results which achieved from analysis, leaded the study to find out the successful interior design and interior atmosphere for retail clothing store. By considering on the results of the study the founding and recommendations were explored. This can lead the study to rich the conclusion of the study which can use for further studies for owners of the clothing stores, interior designers of clothing stores and prospective generations.

ÖZ: Alışveriş, insanların günlük hayatlarının en çekici aktivitelerinden biridir. Mağazalar, bu aktivitenin öneminden dolayı, müsteriler için çok kayda değer bir role sahiptir. Buna koordineli olarak, mağazaların başarılı ortamı müşterileri etkileyip, onlara çekici gelmektedir. Ortam, iç mekanın dilidir. Bu, hiçbir engel olmaksızın direk olarak insanların duygularına verilen değerdir. İnsanlar düşünür, hisseder, hayal kurar ve bu rutin süreç, onların karakteristik özelliklerini belirlemede çok önemli bir unsurdur. Aslına bakılırsa, iç mekan tasarımının amaçlarından biride, iç mekan alanlarının kalitesini yükseltmektir. Bu ortamın yaratılmasına birkaç unsur sebep olmaktadır. Bu unsurların arasında iç mekan tasarımı ve ambians faktörleri direk olarak insanların duygularıyla ilişkilidir. Bu unsurlar herhangi bir mekana anlam verebilir ve insan piskolojisini, duygu ve duyarlarını etkileye bilmektedir. Başarılı bir ortam, kulanıcıları için güven duygusu yaratabilir. Tasarım ve ambians faktörleri bir alanın atmosferini kontrol eden unsurlardır. Bu çalışmada iç mekan tasarımı unsurlarının mağazalar için doğru iç mekanı yaratmanın etkisini araştıracaktır. İlgilenilen genel sorun, kıyafet mağzaları için kullanışlı bir iç mekan ve başarılı bir ortam yaratma bilgisinin eksikliği üzerindedir. Bu çalışmanın amacı, şehirlerin esas alışveriş sokakları boyunca bulunan mağazaların tasarımı için seçenekler bulmaktır. Kıyafet mağazaları iç mekan tasarımı analizleri için, yapılan gözlemler yüzdelikler ile yorumlanıp nicel metod yöntemi kullanılmış, ve literatürdeki bilgilerden yararlanılırken ise nitel metod kullanılmıştır. Literatür üç esas bölüme dayanmaktadır. İlk bölümde mağazalar hakkında genel bilgi, tarihi süreç içerisindeki gelişimi dikkate alınmıştır. Satış mağazalarında bulunabilen farklı fonksiyonlar açıklanmış ve mağazaların ortamlarından bahsedilmiştir. İkinci bölümde kıyafet satış mağazaları hakkında genel bilgi, iç mekan tasarımı ile kıyafet magazaları ilişkisi, ayrıca, cinsiyetin mekan tasarımına etkisi ile mekan algısı kavramlarının iç mekan organizasyondaki ilişkisi irdelenmistir. Çalışmada, Lefkoşa’da bulunan ana alışveriş caddelerinden biri olan Dereboyu ele alınıp incelenmistir. Bu cadde üzerindeki mağazaların iç mekan tasarımı incelenmiştir. Analiz için, Dereboyu caddesinde kadın, erkek ve hem kadın hem erkek kıyafeti satan magazalar seçilmiştir. Analiz sonucunda ortaya çıkan ortalama sonuçlar bu çalışmanın kıyafet satış magazaları için en başarılı ortam ve en uygun iç mekan tasarımınin bulunmasına yol açmıştır. Çalışmamın sonucunda ise; yapılan gözlemler sonucunda çıkan bulgular ele alınıp, alışveris caddesi üzerinde yeni tasarlanacak bir mağaza için önerilerde bulunulmuştur. Bu çalışmanın sonucu, ileriki çalışmalar, kıyafet mağaza sahipleri, kıyafet mağzası iç mimarları ve muhtemel üretimler için kulanılabilir bir sonuca ulaşmaya öncülük edebilir.
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2017. Supervisor: Assist. Prof. Dr. Kamil Guley.
Keywords: Interior Architecture; Stores--Design--Cyprus, North; Clothing store; atmosphere; interior design; design factors and ambient factors